The Representation of Illness in the Fault in Our Stars Directed by Josh Boone: A Psychological Perspective - Wahid, Nazhat Afzha; Widyahening, Evy Tri; Handayani, Sri (Journal of English Language and Education, 2025)
This study examines the representation of illness in The Fault in Our Stars directed by Josh Boone through a psychological perspective. Illness in popular media is often portrayed in a sentimental or stereotypical way, focusing on tragedy or victimhood. This research aims to show how the film frames illness as a meaningful and transformative human experience. The study applies a descriptive qualitative method by conducting close reading of film scenes and dialogues. The analysis is based on Arthur W. Frank’s typology of illness narratives, namely restitution, chaos, and quest. The findings indicate that illness in the film is not only depicted as a medical condition but also as a narrative that shapes identity, relationships, and philosophical views. The quest narrative appears most dominantly, reflecting how the main characters, Hazel Grace and Augustus Waters, find meaning, agency, and emotional growth in the midst of suffering. In conclusion, the film resists stereotypical depictions of illness by presenting resilience, introspection, and authenticity in facing mortality. The novelty of this study lies in applying Frank’s illness narrative theory to film analysis, highlighting how cinematic storytelling can redefine illness as a source of meaning and personal growth.